Simple Acrylic Color Technique for the Preparation of Wet Specimen in Anatomy Museum - Shrestha, Sunil; Yadav, Prabhakar; Mahat, Samyog; Shrestha, Shamsher (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: The subject anatomy is an essential subject in medical college for students and museum with attractive, an innovative colored specimen with well-labeled specimen aids a pivotal role in the teaching and learning process. Once the specimen has been selected for coloring, undergoes fixation, acrylic paint coloring, plastic bottle mounting and proper labeling for better visualization of the structure. Method: We have utilized a simple acrylic color method for painting the gross specimen available for the teaching and learning process from well-embalmed cadavers. The materials required are acrylic color paint, brush, clear nail polish, glycerin, clear plastic bottle, 10% formaldehyde and can be performed at room temperature. Result: The acrylic coloring technique of wet specimen makes specimen attractive which is cost-effective, non-toxic, creates great interest and aids long term memory to the student. Conclusion: The acrylic painted wet gross specimen with clear plastic bottle mounting remains stable in 10% formalin without color fading and makes students a better understanding of the subject.